Survey on the benefits of using memristors for PUFs. Issue 1 (2nd January 2022) - Aljafar, Muayad J.; Acken, John M.
Abstract : This paper reviews memristive PUFs (Physical Unclonable Functions) reported in the literature. The paper explains the motivation for using memristor technology for implementing PUFs. It focuses on PUFs' applications, sizes, analysis, and physical variations. In addition, the paper presents the number of samples generated using Monte Carlo simulation for evaluating the PUF circuits. This paper also describes the protocols, functionality, and methodologies proposed in the memristive PUF literature. Although memristive PUFs are not commercialized yet, there is a high expectation of exploiting the memristors as fundamental elements in the next generation of hardware security primitives (e.g. PUF) due to their unique characteristics such as forming process, temporal drift, nonlinearity, bidirectionality, nonvolatility and model complexity. There have been some survey papers on memristor PUFs in the past, however, the field has continued to develop so a comprehensive survey including recent publications seemed in order at this time. Lately, memristor technology improvement has accelerated, therefore creating a need for an updated survey of the applications of memristors for PUFs. GRAPHICAL ABSTRACT: UF0001